Gambaran Status Gizi dan Kejadian Stunting pada Anak Sekolah Dasar di Daerah Pertanian - Sulistiawati; Suhartono; Bagoes Widjanarko; Alfan Afandi (Pro Health Jurnal Ilmiah Kesehatan, 2025)
Child stunting is a chronic nutritional problem that can inhibit the physical and mental growth and development of children. This study was conducted in shallot farming areas due to the high use of pesticides in the area. The use of pesticides can cause several health impacts, one of which is disrupting the work of growth hormones so that one of them is stunting.  This study aims to determine the description of nutritional status and the incidence of stunting in elementary school children in agricultural areas. The method used was a descriptive observational design with a cross-sectional approach. The research was conducted at SD Dukulo 1 and SD Dukuhlo 2, with samples of grade IV and V students. Data were collected through measurement of body weight and height to assess nutritional status, as well as observation of environmental factors. The results showed that most children had normal nutritional status (82.1%), but 16% were classified as short and 1.9% as very short. Analysis of the relationship between nutritional status and the incidence of stunting revealed that undernutrition and poor nutritional status were closely related to the high incidence of stunting. A total of 18 children with poor nutritional status and 8 children with poor nutritional status were recorded as very stunted. Most of the parents' occupations are in the agricultural sector which allows children to be exposed to pesticides. Pesticides through the growth hormone pathway can cause a child's growth rate to be disrupted, so that any nutritional intake obtained if there is a disturbance in the gastrointestinal tract due to pesticide exposure will cause growth disorders. In conclusion, poor nutritional status can increase the risk of stunting in children, especially in agricultural areas exposed to pesticides. Appropriate nutritional interventions and prevention of harmful environmental exposures are needed.   ABSTRAK                 Stunting pada anak adalah masalah gizi kronis yang dapat menghambat pertumbuhan dan perkembangan fisik serta mental anak. Penelitian ini dilakukan pada daerah pertanian bawang merah dikarenakan pemakaian pestisida yang tinggi pada daerah tersebut. Pemakaian pestisida bisa mengakibatkan beberapa dampak kesehatan salah satunya adalah mengganggu kerja hormon pertumbuhan sehingga berpengarug terhadap pertumbuhan salah satunya adalah stunting.  Penelitian ini bertujuan untuk mengetahui gambaran status gizi dan kejadian stunting pada anak sekolah dasar di daerah pertanian. Metode yang digunakan adalah desain observasional deskriptif dengan pendekatan cross-sectional. Lokasi penelitian dilakukan di Sd Dukulo 1 dan SD Dukuhlo 2, dengan sampel siswa kelas IV dan V. Data dikumpulkan melalui pengukuran berat badan dan tinggi badan untuk menilai status gizi, serta observasi terhadap faktor lingkungan. Hasil penelitian menunjukkan bahwa sebagian besar anak memiliki status gizi normal (82,1%), namun 16% tergolong pendek dan 1,9% sangat pendek. Analisis hubungan antara status gizi dan kejadian stunting mengungkapkan bahwa status gizi kurang dan buruk berhubungan erat dengan tingginya kejadian stunting. Sebanyak 18 anak dengan status gizi kurang dan 8 anak dengan status gizi buruk tercatat mengalami stunting sangat pendek. Sebagian besar pekerjaan orang ua adalah pada sektor pertanian yang memungkinkan anak untuk terpaparar pestisida. Pestisida melalui jalur hormnin pertumbuhan dapat menyebabkan Tingkat pertumbuhan anak terganggu, sehingga berapapuan asupan gizi yang didapatkan jika terjadi gangguan pada saluran cerna karena paparan pestisida akan menyebabkan gangguan pertumbuhan. Kesimpulanya status gizi yang buruk dapat meningkatkan risiko stunting pada anak-anak, khususnya di daerah pertanian yang terpapar pestisida. Intervensi gizi yang tepat dan pencegahan paparan lingkungan yang berbahaya sangat dibutuhkan.